Cenozoic structural history of the Gippsland Basin: Early Oligocene onset for compressional tectonics in SE Australia. (April 2020) - Mahon, Elizabeth M.; Wallace, Malcolm W.
Abstract: The Gippsland Basin contains some of the largest hydrocarbon accumulations in Australia, and has been in production since the 1920's. These hydrocarbons are trapped by large growth anticlines offshore, in reservoirs of the Cretaceous to Eocene-aged Latrobe Group. Despite the obvious importance of these growth anticlines, the timing of their formation, and the overall Cenozoic tectonic history of the basin is not well understood. Here, we present a detailed growth strata analysis of the faults and anticlines within the Cenozoic sediments of the Gippsland Basin. This indicates two major phases of tectonism in the basin: 1. Late Cretaceous to Eocene extension, and 2. Oligocene to Holocene compression. Detailed analysis of the extensional phase indicates the development of numerous normal growth faults, which display an overall reduction in the magnitude of extension from the Late Cretaceous to the Eocene, commonly terminating at the top of the Latrobe Group. The shift to compressional tectonism occurred at approximately the Eocene-Oligocene boundary (~34 Ma). A major and widespread episode of compression then occurred, with evidence of growth on anticlines and reverse faults beginning in the early Oligocene. This previously unrecognized early Oligocene event produced significant growth (20–50% total growth) of the major anticlines which host hydrocarbon accumulations. The early Oligocene event represents the first phase of the compressional tectonic regime that continues to the present day in SE Australia. It appears likely that this Oligocene event affected other basins in SE Australia and probably contributed to uplift of the Eastern Highlands. The underlying tectonic cause for this Oligocene compressional regime is enigmatic and may be related to far field tectonic processes. A second pulse of compressional tectonism and anticline growth occurred during the mid-Miocene and is generally more significant in the onshore regions of the basin. The youngest phase of compressional tectonism beginning in the Late Miocene (~10 Ma) is also more intense in onshore regions and is marked by an unconformity that is widespread in SE Australia. Highlights: Estimates for timing of growth for structures in the Gippsland Basin are made. A change from extension to compression occurs at ~ Eocene-Oligocene boundary. A previously unrecognized early Oligocene tectonic event is documented for SE Australia.